Value chain mapping of the water and sewage treatment to contribute to sustainability - Chofreh, Abdoulmohammad Gholamzadeh; Goni, Feybi Ariani; Zeinalnezhad, Masoomeh; Navidar, Sanaz; Shayestehzadeh, Hamid; Klemeš, Jiří Jaromír (Journal of environmental management, 2019)
Inaccessible hygiene water sources and sanitation are one of the sustainability issues that need to be solved. An attempt to solve this problem is to change the conventional system used in the water supply and sewage treatment to sustainable water and waste management. To transform the system, companies initially need to map their business value chain. However, this process is often not receiving a full attention by the organisation. In an academic perspective, there are limited studies that map the value chains of water and waste systems. To overcome this limitation, the present study aims to map the value chain processes of the water and wastewater utility companies towards a sustainability solution. A review of related studies is used to conduct this study. Khuzestan Urban Water and Sewage company in Iran has been selected as case studies. The mapping results indicate a lack of sustainability integration in a water management system that leads to ineffective and inefficient water management. Value chain mapping process is significant for practitioners, particularly in the water and sewage companies, as a starting point for transforming their conventional water management systems towards sustainability. Experts at the company stated that value chain mapping as part of value chain analysis enables organisations to increase operational efficiency and eliminate waste by 57%.
Keywords: voda; odpad tekutý - odstraňování; Waste Disposal, Fluid; odpadní vody; Transformation; Water and sewage; odpadní voda; Waste Water; Írán; Iran; Sewage; Value chain; Mapping; Wastewater; Sustainability; Water